PELATIHAN MASA DEPAN UNTUK HARAPAN DAN KETERAMPILAN SOSIAL PADA SANTRI - Nur'aini Azizah; Neina Qonita Istiqomah; Fina Yunia Asih (JIP (Jurnal Intervensi Psikologi), 2023)
Abstract : Boarding students in adolescence age is prone to experience crisis related to future preparedness and social interaction problems. This study aims to examine the effectiveness of training programs in increasing hope and social skills in students. This study used an experiment with a pretestposttest control group design. Participants were 96 students who were divided into control and experimental groups, each consisting of 47 and 49 participants. The data were analyzed using the paired sample T-test which showed that there was a significant difference in the scores of social skills and hope between the pretest and posttest in the experimental group. The results of the analysis show that there is an increase in hope and social skills of the students who took part in the training program or the experimental group.